Phytosociological survey of weeds in the grapevine - Ronaldo Luiz Rassele; Silvério de Paiva Freitas; João Nacir Colombo; Marcelo Rodrigo Krause; Heitor Barth; Henrique Teodoro Barth (Bioscience Journal, 2022)
Viticulture is expanding in the state of Espírito Santo, Brazil. Weed management is essential for the crop, so knowing the floristic composition of weeds in the vineyards makes this practice sustainable. This study aimed to evaluate the floristic composition of weed populations in grape crops in two seasons, considering different altitudes. The experiment was performed in four properties located in Santa Teresa, ES, Brazil, two of which were at altitudes above 500 m of and two below 500 m, in the winter (2018) and summer (2019) seasons. Weeds were identified with the square inventory method. The phytosociological analysis was based on absolute and relative parameters of frequency, density, dominance, importance value index, and relevance index, besides the diversity, evenness, and similarity indices. Fifty species, 41 genera, and 19 families were identified. The most representative families regarding the number of species were Asteraceae, Poaceae, and Malvaceae. In properties with higher altitudes, the species with the highest IVI was Pilea microphylla (L.) Liebm., in both seasons. In properties with lower altitudes, the highest IVI values were found for Malvastrum coromandelianum L. in the winter and Commelina benghalensis and Portulaca oleracea L. in the summer. The areas below 500 m of altitude showed the highest diversity and evenness indices. The proximity between the areas in both regions contributed to the increased similarity index. Altitude and time of the year contribute to the composition of the infesting community.